If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 = -2r + -6 Reorder the terms: -4 = -6 + -2r Solving -4 = -6 + -2r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '2r' to each side of the equation. -4 + 2r = -6 + -2r + 2r Combine like terms: -2r + 2r = 0 -4 + 2r = -6 + 0 -4 + 2r = -6 Add '4' to each side of the equation. -4 + 4 + 2r = -6 + 4 Combine like terms: -4 + 4 = 0 0 + 2r = -6 + 4 2r = -6 + 4 Combine like terms: -6 + 4 = -2 2r = -2 Divide each side by '2'. r = -1 Simplifying r = -1
| 9x+3=81 | | 2/3x=3/5 | | -25+48/12+4-6 | | -8x-38=-7(4x-6) | | 5x-y=19 | | 2x^2-3x-3.125=0 | | 25+7c=45 | | -5x-(2x-4)=3x-6 | | 17=2(3.14)r | | -44=4t+8 | | 2x^2-3x+1.125=0 | | 12+x=-27 | | -6(8+6n)=20-2n | | 2sec^2x+tanx=8 | | 4m+5-2m=3m-6 | | x-4x+3=-2x+8 | | X/-9=-3 | | -28(-3)= | | wyz=x-z-wz | | 2(r-3)=6 | | 34x-787=89x | | -8(8x-6)+1=-4x-11 | | x=3x+b | | 3x^2-2x-14=-6 | | 4(4x-2)+5=x-3 | | 1/2(-10)+(-10)/5+12/4 | | 0.17x/19=0.13x/25 | | -3(3a+15)-(10+a)=35 | | 18x^2+62x-24=-4x | | 1/3(6n-33)=7-4n | | 5-9+(-2)*4/2 | | 7a-3(4a+8)=11 |